2015
DOI: 10.2196/publichealth.3310
|View full text |Cite
|
Sign up to set email alerts
|

The Digital Distribution of Public Health News Surrounding the Human Papillomavirus Vaccination: A Longitudinal Infodemiology Study

Abstract: BackgroundNew media changes the dissemination of public health information and misinformation. During a guest appearance on the Today Show, US Representative Michele Bachmann claimed that human papillomavirus (HPV) vaccines could cause “mental retardation”.ObjectiveThe purpose of this study is to explore how new media influences the type of public health information users access, as well as the impact to these platforms after a major controversy. Specifically, this study aims to examine the similarities and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 22 publications
1
24
0
1
Order By: Relevance
“…Despite some research demonstrating that Web-based vaccine information can have a largely negative sentiment [11], our findings show that a great percentage of tweets about HPV vaccine had a positive sentiment, helping to validate findings on the same topic [24-27]. Furthermore, over one-quarter of these positive HPV vaccine tweets mentioned prevention or protection.…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…Despite some research demonstrating that Web-based vaccine information can have a largely negative sentiment [11], our findings show that a great percentage of tweets about HPV vaccine had a positive sentiment, helping to validate findings on the same topic [24-27]. Furthermore, over one-quarter of these positive HPV vaccine tweets mentioned prevention or protection.…”
Section: Discussionsupporting
confidence: 38%
“…Researchers are just beginning to assess the extent and type of discourse about the HPV vaccine on Twitter, although methods are varied [24-27]. This emerging area of communication research provides an opportunity for interdisciplinary teams among the fields of public health, health communication, and data science to strengthen the science and methodology in this growing area of research.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies have independently examined responses on Twitter to specific controversial events including US Representative Michele Bachmann’s claim that HPV vaccines could cause ‘mental retardation’ and Katie Couric’s television segment ‘HPV Vaccine Controversy’ that aired on 4 December 2013. 53 75 Mahoney et al evaluated 200 social media posts before and after Bachmann’s comments on the Today Show and found that though most media was positive in tone, compared with Google News, Twitter disseminated more positive HPV vaccine articles and also used more personal accounts as a reference source. 53 In contrast, using a random sample of 3595 tweets, Bahk et al found that most sentiment on Twitter towards HPV vaccines before Katie Couric’s episode was negative, and while there was a decrease of negative sentiment immediately after the show aired, negative sentiment returned to baseline after 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Examples that are relevant to our research include the use of topic modeling to extract tobacco-related tweets in the United States [ 18 ] and the surveillance of information about the misunderstanding and misuse of antibiotics from online media [ 19 ]. There is a growing area of research considering the spread of information, news, and opinions about vaccines [ 20 - 24 ], and research in this area focuses on measuring associations between misinformation, beliefs, and decision making across a range of community health practices [ 25 ].…”
Section: Introductionmentioning
confidence: 99%